2021
DOI: 10.1042/bsr20210260
|View full text |Cite
|
Sign up to set email alerts
|

Urinary l-erythro-β-hydroxyasparagine—a novel serine racemase inhibitor and substrate of the Zn2+-dependent d-serine dehydratase

Abstract: In this study, we identified L-erythro-β-hydroxyasparagine (L-β-EHAsn) found abundantly in human urine, as a novel substrate of Zn2+-dependent D-serine dehydratase. L-β-EHAsn is an atypical amino acid present in large amounts in urine but rarely detected in serum or most organs/tissues examined. Quantitative analyses of urinary L-β-EHAsn in young healthy volunteers revealed significant correlation between urinary L-β-EHAsn concentration and creatinine level. Further, for in-depth analyses of L-β-EHAsn, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These works also resulted in the finding of a new unknown substrate for Dsd1p in urine. In this paper [5], Ito et al initially found that the new Dsd1p substrate is the amino acid β-hydroxyl asparagine. For this, they have analysed the amino acid contents in urine using a cascade of coupled reactions employing enzymes that recognise d-amino acids (Dsd1p and DAAT).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…These works also resulted in the finding of a new unknown substrate for Dsd1p in urine. In this paper [5], Ito et al initially found that the new Dsd1p substrate is the amino acid β-hydroxyl asparagine. For this, they have analysed the amino acid contents in urine using a cascade of coupled reactions employing enzymes that recognise d-amino acids (Dsd1p and DAAT).…”
Section: Commentarymentioning
confidence: 99%
“…These works also resulted in the finding of a new unknown substrate for Dsd1p in urine. In this paper [ 5 ], Ito et al . initially found that the new Dsd1p substrate is the amino acid β-hydroxyl asparagine.…”
Section: Commentarymentioning
confidence: 99%